2022
DOI: 10.3390/w14203239
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Air for the Mire-Breathing Hypothesis: Sphagnum Moss and Peat Structure Regulate the Response of CO2 Exchange to Altered Hydrology in a Northern Peatland Ecosystem

Abstract: Sphagnum-dominated peatlands store more carbon than all of Earth’s forests, playing a large role in the balance of carbon dioxide. However, these carbon sinks face an uncertain future as the changing climate is likely to cause water stress, potentially reducing Sphagnum productivity and transitioning peatlands to carbon sources. A mesocosm experiment was performed on thirty-two peat cores collected from two peatland landforms: elevated mounds (hummocks) and lower, flat areas of the peatland (hollows). Both rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, studies that have used peat cores covered only by Sphagnum record higher CO 2 release during drainage (WT = -40 cm) than during slow rewetting (WT = -25 and -20 cm), due to increased R eco associated with higher microbial activity (Blodau & Moore, 2003;Strack & Price, 2009). reduces moss productivity, increases their autotrophic respiration, and increases R eco rates, generating higher CO 2 emissions to the atmosphere (Figure 6; Table 1; Table S1) (Blodau et al, 2004;O'Neill et al, 2022;Riutta et al, 2007;Tuittila et al, 2004). We generated this consensus cautiously due to some contradictory results reported in the literature, indicating increases, decreases, or low differences in Sphagnum photosynthesis rates and R eco associated with drainage (Huang et al, 2021;Kokkonen et al, 2022;Ma et al, 2022), a condition related to the complexity of the variables involved, and to the difficulty of identifying a unifying mechanism for NEE responses considering the multiple interactions between biotic and abiotic components in a peatland (Huang et al, 2021;Laiho, 2006;Laiho et al, 2004).…”
Section: Impact Of Drainage On Ecosystem Respiration (R Eco ) In Peat...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies that have used peat cores covered only by Sphagnum record higher CO 2 release during drainage (WT = -40 cm) than during slow rewetting (WT = -25 and -20 cm), due to increased R eco associated with higher microbial activity (Blodau & Moore, 2003;Strack & Price, 2009). reduces moss productivity, increases their autotrophic respiration, and increases R eco rates, generating higher CO 2 emissions to the atmosphere (Figure 6; Table 1; Table S1) (Blodau et al, 2004;O'Neill et al, 2022;Riutta et al, 2007;Tuittila et al, 2004). We generated this consensus cautiously due to some contradictory results reported in the literature, indicating increases, decreases, or low differences in Sphagnum photosynthesis rates and R eco associated with drainage (Huang et al, 2021;Kokkonen et al, 2022;Ma et al, 2022), a condition related to the complexity of the variables involved, and to the difficulty of identifying a unifying mechanism for NEE responses considering the multiple interactions between biotic and abiotic components in a peatland (Huang et al, 2021;Laiho, 2006;Laiho et al, 2004).…”
Section: Impact Of Drainage On Ecosystem Respiration (R Eco ) In Peat...mentioning
confidence: 99%
“…On the other hand, experiments with Sphagnum mesocosms obtained from different microtopographic positions of a bog located in Michigan (USA) showed that, under drainage conditions (WT = −25 cm), the GPP of mosses established in hollows was more affected than those forming hummocks, increasing CO 2 emissions in the former (O'Neill et al, 2022). Hummock-forming mosses offer greater resistance to maintain GPP under drainage conditions thanks to a high capitulum density and increased capillary transport efficiency in water retention, allowing them to respond favorably to water stress, while retaining stability in C fluxes (Adkinson & Humphreys, 2011;Bengtsson et al, 2016;O'Neill et al, 2022;Robroek et al, 2009). In general, Sphagnum gross photosynthesis exhibits a unimodal response to WT variation (Tuittila et al, 2004), in which case different studies indicate that its optimal position should be maintained between −5 and −20 cm to maximize moss GPP (Brown et al, 2017;Riutta et al, 2007;Tuittila et al, 2004) (Figure 5).…”
Section: Impact Of Drainage On Gross Primary Productivity (Gpp) Of Sp...mentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that sphagnum-dominated peatlands store more carbon than all the Earth's forests, thus playing an important role in the carbon balance of the planet [12]. About 90% of the peatlands of Western Siberia belong to peat bogs with a predominance of sphagnum.…”
Section: Introductionmentioning
confidence: 99%